Effects of Ursolic Acid on Intestinal Health and Gut Bacteria Antibiotic Resistance in Mice - Peng, Fang; Zhang, Haihan; He, Xi; Song, Zehe (Frontiers in Physiology, 2021)
Ursolic acid (UA), a natural pentacyclic triterpenoid, has been widely reported to exert great anti-oxidant and anti-inflammatory properties. However, the effects of UA on the intestinal homeostasis and gut microbiota were rarely explored. The present study was to investigate the effects of UA on intestinal health and gut microflora antibiotic-resistance in antibiotic-exposed mice. Eighty Kunming mice were randomly allocated into three groups and fed with one of the following diets respectively: Cont group, the basal diet; UA group, the basal diet supplemented with 150mg/kg UA; Tet group, the basal diet supplemented with 659mg/kg chlortetracycline. After 14 days, 10 mice in each group were euthanatized and the remaining 30 mice in the Tet group were equally allocated into three sub-groups as follows: the Tet group which were kept feeding a Tet diet for 14 days; the Natural Restoration (NatR) group which received a basal diet for 14 days; and the UA therapy (UaT) group which fed a basal diet supplemented with 150mg/kg UA for 14 days. The results showed that UA treatment significantly increased ADFI of mice. Notably, UA increased the jejunal villi height, decreased the jejunal crypt depth and promoted the expression of jejunum nutrient transporters. UaT group had higher villi height, lower crypt depth and higher nutrient transporter mRNA expression in jejunum than NatR group. Besides, UA decreased serum DAO content, upregulated mRNA expression of ZO-1, claudin-1 and occludin and downregulated TNF-α and IL-6. The mRNA abundances of ZO-1, claudin-1 and occludin and TNF-α and IL-6 in UaT group were respectively upregulated and downregulated than NatR group. Furthermore, an analysis of 16S rDNA sequences demonstrated that UA increased the abundance of beneficial bacteria in the gut. And the results of ARG test showed that UA downregulated the expression of antibiotic-induced resistance genes. The UaT group inhibited the increase of harmful bacteria abundance and suppressed the mRNA abundances of TRGs compared to the NatR group. In conclusion, considering the positive effects of UA on the growth performance and intestinal mucosal barrier, we anticipate that these findings could be a stepping stone for developing UA as a novel substitute of antibiotics.